Intestinal health improvement with protected organic acids and essential oils for pullets raised under field conditions - Vieira, Marcia de Souza; Moraes, Mariana Lemos de; Stefanello, Thais Bastos; Bertolini Junior, Francisco; Silva, Guilherme Moreira de Melo; Tavares, João Marcos Novaes; Nakamatsu, Carlos Yassuharu; Arantes, Leticia Cury Rocha Veloso; Santin, Elizabeth (Frontiers in Animal Science, 2022)
We investigated the dietary supplementation of protected organic acids and essential Oils P(OA+EO) in pullets raised under commercial conditions. A total of 208,000 pullets Lohmann at 2-weeks-old were assigned to receive 1 of 2 treatments: T1, control diet used in the farm; T2, control diet and P(OA+EO) at 300 g/t (fumaric, sorbic, citric and malic acids + thymol, eugenol and vanillin microencapsulated in hydrogenated vegetable fat - Jefo Nutrition Inc. Canada). P(OA+EO) was supplemented from 2 to 18 weeks and the trial lasted 21 weeks. At weeks 6, 12 and 21, 12 pullets/treatment were used for blood sampling and necropsy for ISI – I See Inside. A completely randomized design consisting of 2 treatments, each with 12 replicates of 1 hen/replicate, was used. To evaluate intestinal integrity, birds were inoculated with fluorescein-isothiocyanate labelled dextran (FITC-d) and blood samples were collected after 1.5 h. The macroscopic ISI score of alterations were classified to be presented as: overall health ISI (sum of the scores assigned for intestine, liver, proventriculus, annex glands, locomotor, and respiratory systems) and macro-intestinal ISI (sum of the scores assigned for duodenum, jejunum, ileum, and cecum). The histologic intestinal ISI alterations were evaluated in the ileum. A low ISI index represents better health status. Pullets on P(OA+EO) had lower (P< 0.001) levels of FITC-d recovered in the blood, which is related to reduced leaky gut. They also presented lower overall health ISI score at weeks 6 (P = 0.002) and 12 (P = 0.003), lower macro intestinal ISI score at weeks 6 (P = 0.0001) and 21 (P = 0.004) and, lower histologic intestinal ISI score of alterations at weeks 6 (P = 0.09), 12 (P = 0.0006), and 21 (P< 0.0001), which is associated to better overall health. In addition, at week 21, pullets on P(OA+EO) did not present Eimeria oocysts while the control treatment did (P< 0.0001). In conclusion, the blend of protected organic acids and essential oils evaluated can be used to improve intestinal and overall health status in commercial pullets.